PKM Pelatihan Bimbingan Karir Pencegahan Anak Putus Sekolah pada Kelompok Guru BK di Kabupaten Sidrap - Abdullah Sinring; Nur Fadhilah Umar (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Based on the results of the FGD and interviews with BK teachers and students in Turikale sub-district, information was obtained that training related to career guidance for BK teachers at SMP / Mts to prevent children from dropping out of school was still very low. In addition, the results of interviews with counseling teachers show that 52% of BK services are dominated by tutoring, 35% for personal-social services and 12% for career guidance services. The results of interviews with counseling teachers obtained information that the implementation of career guidance only uses the lecture method in all situations without paying attention to students and the material given. As a result, students tend to neglect following career guidance and have low career expectations in the future. Based on the above background, it is deemed necessary to provide career guidance training for BK teachers at SMP / Mts in order to prevent children from dropping out of school. The implementation of this PKM is carried out by adopting action research steps consisting of 5 stages, namely: planning, action, observation, evaluation and reflection and mentoring. This training activity will be carried out for 4 days of this activity, and will be given assistance after the activity for 3 months. The target participants in this activity are 40 BK teachers. There are several outputs that will be produced through this program, namely 1) Scientific Publications in the Journal "Indonesian Journal of Educational Studies" Indexed in DOAJ, Google Scholar, SINTA, and others. 2) Publication in print / electronic media (Makassar City News, Tribun Timur, and UNM Website) and in the form of video activities, 3) Increasing understanding of BK Teachers regarding methods in career guidance, 4.) Counseling teachers can develop / practice various methods various career guidance. Other outputs that can be generated through this activity are increasing student career expectations and improving the quality of BK services in schools, especially in SMP / Mts. This Community Partnership Program (PKM) aims to assist target partners in resolving problems regarding reduced production and decreased selling value of seaweed. The steps taken to overcome partner problems are taken through 1) Counseling, discussion, and assistance regarding microcontroller technology that can be applied to increase partner seaweed production. 2) Training on the manufacture and use of water salinity control systems, as well as counseling on various handling strategies if the pond location is far from rivers / sea. 3) Counseling and training on business management and marketing so that the selling value of partner seaweed can increase